(untitled) (Journal of Philosophy Culture and Political Science, 2019)
Today, in the context of democratization and humanization of public life, there is a need to improve the spiritual culture that determines national characteristics. Today in Kazakhstan, which has embarked on the path of independence and started to realize the goal of becoming one of the fifty civilized countries, one of the most important tasks is the formation of national consciousness and national Outlook of the people of Kazakhstan. Therefore, all activities carried out in the country contribute to raising the level of education and training of young people in the spirit of universal and national values. Currently, special attention is paid to the history of spiritual culture. One of the deepest and most comprehensive thinkers who have made a significant contribution to the spiritual culture and philosophy of the Kazakh people is Abay Kunanbayev. The basis of the creative heritage of Abay, who lived in a difficult time of the last century, but despite this has risen to a high level of global thinking , are deep philosophical concepts. In order to understand the meaning of Abay’s creativity, it is necessary to know that Abay, whose creativity is based on knowledge and teaching, is one of the most popular thinkers for the people. Key words: humanism, morality, value, «edifying words», faith, spirituality.